Perwujudan Brand Image dalam Penataan Interior Rotelli Shoes di Galaxy Mall - Maria Sulistya C.; Sriti Mayang Sari (Intra, 2013)
Nowadays the economic developmentis increasing in Surabaya. This has a positive impact on retail companies in Surabaya. In order to remain competitive shop among many other stores, they need a unique interior design, comfortable and functional that can attract customers to shop. An attractive interior design alone is not enough, however they need an interior design that canreflect the image and strategies.Rotelli is one of the famous shoesbrand from Italy and has a vision to be a trendsetter in the field of women's fashion shoes in Indonesia. This study aims to determine whether the interior design of Rotelli reflects their brand image, which has an elegant, exclusive and comfortable concept and describe the application of brand image through interior design, color and materials they used.The final result is Rotelli is one of the brand that priorities their interior design’s shop and has a strong brand image. This is applicated through the interior arrangement is comfortable and supportive shopping activities, colors and materials that reflect the brand image of Rotelli.